2012
DOI: 10.1007/s10584-012-0483-8
|View full text |Cite
|
Sign up to set email alerts
|

Current state and trends in Canadian Arctic marine ecosystems: II. Heterotrophic food web, pelagic-benthic coupling, and biodiversity

Abstract: As part of the Canadian contribution to the International Polar Year (IPY), several major international research programs have focused on offshore arctic marine ecosystems. The general goal of these projects was to improve our understanding of how the response of arctic marine ecosystems to climate warming will alter food web structure and ecosystem services provided to Northerners. At least four key findings from these projects relating to arctic heterotrophic food web, pelagic-benthic coupling and biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 101 publications
8
69
0
Order By: Relevance
“…2 or Table 2) was similar to those reported earlier from the region (2003)(2004)2008) (Darnis et al, 2012;Link et al, 2011;Renaud et al, 2007b). All those studies reported highest uptake off the Mackenzie Delta and the Cape Bathurst polynya.…”
Section: Ineffectiveness Of Oxygen Flux As Proxy For Spatial Patternssupporting
confidence: 90%
See 2 more Smart Citations
“…2 or Table 2) was similar to those reported earlier from the region (2003)(2004)2008) (Darnis et al, 2012;Link et al, 2011;Renaud et al, 2007b). All those studies reported highest uptake off the Mackenzie Delta and the Cape Bathurst polynya.…”
Section: Ineffectiveness Of Oxygen Flux As Proxy For Spatial Patternssupporting
confidence: 90%
“…Benthic boundary fluxes of silicic acid, oxygen and phosphate in 2009 were in the range of those reported for the region in 2008 (Darnis et al, 2012). It is noteworthy that phosphate was released from shallow Mackenzie Shelf sediments during the upwelling year 2008 and that notably less silicic acid was remineralised in the Cape Bathurst polynya area in 2008.…”
Section: Ineffectiveness Of Oxygen Flux As Proxy For Spatial Patternsmentioning
confidence: 55%
See 1 more Smart Citation
“…A decline in spawning and foraging areas will affect both predators and their prey. For instance, polar cod (Boreogadus saida) abundance might be significantly reduced, with tremendous consequences to the entire system as this species is believed to account for up to 75% of energy transfer between zooplankton and vertebrate predators (Darnis et al 2012). In addition to changes in resource availability, top predators will likely face increased complexity within food webs that tend to dissipate energy flow (Węsławski et al 2009).…”
Section: Upper Trophic Levelsmentioning
confidence: 99%
“…(1.1 mm) (Darnis et al, 2012). Following the current dynamics, the boreal species C. finmarchicus is also regularly found in marginal Arctic seas, especially in the eastern Greenland Sea and Barents Sea (Conover and Huntley, 1991).…”
Section: Introductionmentioning
confidence: 97%